A dynamic, spatially periodic, micro‐pattern of HES5 underlies neurogenesis in the mouse spinal cord. Issue 5 (25th May 2021) - Biga, Veronica; Hawley, Joshua; Soto, Ximena; Johns, Emma; Han, Daniel; Bennett, Hayley; Adamson, Antony D; Kursawe, Jochen; Glendinning, Paul; Manning, Cerys S; Papalopulu, Nancy
Abstract: Ultradian oscillations of HES Transcription Factors (TFs) at the single‐cell level enable cell state transitions. However, the tissue‐level organisation of HES5 dynamics in neurogenesis is unknown. Here, we analyse the expression of HES5 ex vivo in the developing mouse ventral spinal cord and identify microclusters of 4–6 cells with positively correlated HES5 level and ultradian dynamics. These microclusters are spatially periodic along the dorsoventral axis and temporally dynamic, alternating between high and low expression with a supra‐ultradian persistence time. We show that Notch signalling is required for temporal dynamics but not the spatial periodicity of HES5. Few Neurogenin 2 cells are observed per cluster, irrespective of high or low state, suggesting that the microcluster organisation of HES5 enables the stable selection of differentiating cells. Computational modelling predicts that different cell coupling strengths underlie the HES5 spatial patterns and rate of differentiation, which is consistent with comparison between the motoneuron and interneuron progenitor domains. Our work shows a previously unrecognised spatiotemporal organisation of neurogenesis, emergent at the tissue level from the synthesis of single‐cell dynamics. Synopsis: Live imaging of HES5 expression in the ventral mouse spinal cord combined with computational modelling is used to identify and analyse spatially periodic HES5 micro‐patterns that emerge from the synthesis of single cell dynamics. HES5 is expressed in spatially periodic microclusters along the dorsal‐ventral axis, dynamically maintained by Notch signalling. Microclusters can arise, in part, from single cell oscillators that are synchronous and weakly coupled via Notch. Spatial patterns differ between motorneuron and interneuron progenitor domains and the probability for progenitor differentiation is regulated by the coupling strength between cells. NGN2 is also spatially periodic along the dorso‐ventral axis and HES5 microclusters may act to select a single NGN2‐high cell for differentiation. Abstract : Live imaging of HES5 expression in the ventral mouse spinal cord combined with computational modelling is used to identify and analyse spatially periodic HES5 micro‐patterns that emerge from the synthesis of single cell dynamics.